The Effect of Environmental Accounting Implementation on Company Performance - Marisa Yunita Br Depari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The method used in this study is library research. From this study, it could be concluded that environmental accounting had an impact on company performance. This study aims to determine the effect of the implementation of environmental accounting on company performance through analysis of various impacts on company performance, such as increasing costs and decreasing corporate profits, improving company performance, reducing performance damage that often resembles precision and even the impact that shows habits on company performance.The research implication of this study for the development of science is as a material consideration for companies in implementing environmental accounting as a solution to overcome environmental problems